Sexuality is associated with the quality of life of the elderly! - Edison Vitório de Souza Júnior; Benedito Fernandes da Silva Filho; Vinicius Santos Barros; Átila Rodrigues Souza; Jéssica Ribeiro de Jesus Cordeiro; Lais Reis Siqueira; Namie Okino Sawada
ABSTRACT Objective: to analyze the association between sexuality and quality of life of Brazilian elderly residents in the community. Methods: a cross-sectional study conducted with 477 Brazilian elderly. The data were collected between August and October 2020. We used the EVASI and WHOQOL-OLD (World Health Organization Quality of Life). Data analysis was performed with Mann-Whitney, Spearman and Kruskal-Wallis correlation tests, with Bonferroni post-hoc application when necessary, considering a 95% confidence interval. Results: there was a statistical association between all dimensions of sexuality and the general quality of life of the elderly (p<0.05). Conclusion: the stimulation of sexuality can be configured as an innovative and holistic strategy focused on the promotion of health and active aging, since this study found the association between sexuality and the general quality of life of elderly people.